2010
DOI: 10.5194/bg-7-1515-2010
|View full text |Cite
|
Sign up to set email alerts
|

Variations in chemical and physical properties of Amazon forest soils in relation to their genesis

Abstract: Soil samples were collected in six South American countries in a total of 71 different 1 ha forest plots across the Amazon Basin as part of the RAINFOR project. They were analysed for total and exchangeable cations, C, N, pH with various P fractions also determined. Physical properties were also examined and an index of soil physical quality proposed. A diverse range of soils was found. For the western areas near the Andean cordillera and the southern and northern fringes, soils tend to be distributed among th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
526
2
11

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 422 publications
(561 citation statements)
references
References 83 publications
22
526
2
11
Order By: Relevance
“…The nil effect of the mineral nutrient treatments was unexpected because the highly-weathered Amazonian soils are of low fertility (Sanchez, 1976;Quesada et al, 2010). However, our results agree with Cleveland et al (2011), who found only a weak correlation between P and net primary production.…”
Section: Effect Of Nutrient Additionsupporting
confidence: 58%
“…The nil effect of the mineral nutrient treatments was unexpected because the highly-weathered Amazonian soils are of low fertility (Sanchez, 1976;Quesada et al, 2010). However, our results agree with Cleveland et al (2011), who found only a weak correlation between P and net primary production.…”
Section: Effect Of Nutrient Additionsupporting
confidence: 58%
“…32,43 Hicks et al suggested that BS of 20% could be used as a threshold for predicting damage due to acidification. 4 Low BS in the tropics is likely tightly linked to high rates of weathering and leaching, 44,45 arising from the humid tropical climate with high rainfall and temperatures that favor rapid dissolution and leaching of weatherable minerals.…”
Section: Characteristics Of Soil Buffering Capacity In Tropicalmentioning
confidence: 99%
“…Ferralsols and Acrisols are found along the slopes and plateaux, which are highly weathered and have favourable physical conditions (i.e. stable aggregate structure, associated with good drainage) (Chauvel et al 1987;Quesada et al 2010). Near streams and valley bottoms, wet and sandy soils (Podzols) occur, but these were not included in this study.…”
Section: Study Sitesmentioning
confidence: 99%
“…Phillips et al 2009;Negrón-Juárez et al 2010) and to long-term differences in forest dynamics in response to environmental characteristics (Keller et al 2004;Malhi et al 2006;Chao et al 2009a). Soils represent an important environmental gradient in Amazonia, with a wide variety of soil types across the Basin and with diverse chemical and physical conditions (Quesada et al 2010;. Variations in soil physical properties across the Basin have been related to a large proportion of the variation in tree turnover rates and mean forest wood density, with disturbance levels and vegetation structure of Amazonian forests being related to different soil types (Quesada et al 2012).…”
Section: Introductionmentioning
confidence: 99%